Responsible Innovation Practices, Green Human Resource Management, and Organizational Sustainability in Indonesia’s Public Sector - Yakup; Olfin Ishak; Firman Dera (Journal of Economics and Management, 2026)
Organizational sustainability has become a strategic priority for public-sector organizations, yet empirical evidence explaining how Responsible Innovation Practices (RIP) enhance sustainability through Green Human Resource Management (GHRM) remains limited, particularly in developing countries. This study analyzes the direct and indirect associations among RIP, GHRM, and Organizational Sustainability (OS) in the Indonesian public sector. To achieve this objective, the study adopted a quantitative explanatory research design and used survey responses from 300 civil servants and managers employed by the Provincial Government of Gorontalo. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that Responsible Innovation Practices positively affect Green Human Resource Management and Organizational Sustainability. Furthermore, Green Human Resource Management significantly improves Organizational Sustainability while partially mediating the influence of Responsible Innovation Practices on sustainability outcomes. These findings extend Responsible Innovation Theory by demonstrating that the effectiveness of responsible innovation depends on organizational capabilities embedded in sustainability-oriented human resource practices. The study also supports Stakeholder Theory, the Ability-Motivation-Opportunity (AMO) framework, and the Natural Resource-Based View (NRBV) in explaining sustainability transformation in public-sector organizations. Practically, public institutions should integrate responsible innovation with sustainability-oriented human resource management to strengthen long-term organizational sustainability.